LEGAL RESPONSIBILITY FOR THE USE OF UNMANNED AIRCRAFT SYSTEMS FOR MILITARY PURPOSES - Vodolaskova, Kateryna (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
The purpose of the article is to explore the current sense of uncertainty regarding applicable legal standards, the rapid development and proliferation of unmanned aerial vehicles and robotic technologies due to the perceived lack of transparency and accountability of current policies, which can polarize the international community, undermine the rule of law and ultimately destabilize the security of the international environment as a whole. Research methods: the study is based on scientific and specifically legal methods of knowledge, which were used to analyze doctrinal approaches to the development of ideas regarding the understanding of the concept and essence of unmanned aerial vehicles, their use for military purposes, and legal responsibility for violations of humanitarian law. One of the main methods used is the dialectical method of cognition, which made it possible to establish and distinguish the qualitative characteristics of the studied phenomenon. Thanks to a special legal method, the norms of humanitarian law were investigated with the aim of calling for the full, fair and effective use of the law enforcement mechanism in order to bring to legal responsibility all those involved in the use of unmanned systems in the military by a terrorist country on the territory of Ukraine. Results: Ukraine, as a part of Europe, is fighting for modern and future principles of the rule of law, the rule of law and the protection of human rights. At the same time, the terrorist country uses the latest technologies for an aggressive appeal to the principles of the past, which is based on the mutilation of humane principles, uses labor cases and the greatest manifestations of the Middle Ages and the rules of ancient nomadic tribes. Ukraine hopes that international humanitarian law and the law of war will be applied fairly, effectively and as quickly as possible to bring to justice all those involved in a terrorist country that uses the latest technologies to commit crimes against humanity. Discussion: Since the full-scale invasion of the northern neighbor on the territory of Ukraine, interest in all types of UAVs has grown in a special way. This war demonstrated the combat advantages of drones, which have become smaller, more lethal, easier to operate, and available to almost everyone. However, there are also gaps in the application of the legal responsibility of those involved in the use of drones to violate international humanitarian law rights.